C4 Photosynthesis and related CO2 concentrating mechanisms - Raghavendra, Agepati S.; Sage, Rowan F. (Springer eBooks., 2011)
The C4 pathway of photosynthesis was discovered and characterized, more than four decades ago. Interest in C4 pathway has been sustained and has recently been boosted with the discovery of single-cell C4 photosynthesis and the successful introduction of key C4-cycle enzymes in important crops, such as rice. Further, cold-tolerant C4 plants are at the verge of intense exploitation as energy crops. Rapid and multidisciplinary progress in our understanding of C4 plants warrants a comprehensive documentation of the available literature. The book, which is a state-of-the-art overview of several basic and applied aspects of C4 plants, will not only provide a ready source of information but also triggers further research on C4 photosynthesis. Written by internationally acclaimed experts, it provides an authoritative source of progress made in our knowledge of C4 plants, with emphasis on physiology, biochemistry, molecular biology, biogeography, evolution, besides bioengineering C4 rice and biofuels. The book is an advanced level textbook for postgraduate students and a reference book for researchers in the areas of plant biology, cell biology, biotechnology, agronomy, horticulture, ecology and evolution.